PENGARUH MODEL PEMBELAJARAN INKUIRI TIPE PICTORIAL RIDDLE TERHADAP PRESTASI BELAJAR IPA KELAS VIII SMP 2 BANGUNTAPAN BANTUL - Semiyatun Semiyatun; Hidayati Hidayati; Astuti Wijayanti (N A T U R A L: Jurnal Ilmiah Pendidikan IPA, 2015)
The descriptive research aims to understand a tendency of study science achievement in student of class VIII Banguntapan 2 Junior High School in 2015/2016. This research uses inquiry which is type of Pictorial Riddle and expository model. The comparative research aims to understand a difference of study science achievement in student of class VIII Banguntapan 2 Junior High School in 2015/2016 with uses inquiry of Pictorial Riddle and Expository model. This method of research is a Quasy Experiment. The result of descriptive research is to show a tendency of science study achievement in student of class VIII Banguntapan 2 Junior High School in 2015/2016 which uses Pictorial Riddle is the highest category than Expository model. Then, the result of comparative research, there is difference of science study achievement in student of class VII Banguntapan 2 Junior High School which uses Pictorial Riddle and Expository model. So that there is an influence in an inquiry which is type of Pictorial Riddle toward a science study achievement in student of VIII Banguntapan 2 Junior High School in 2015/2016.